Increasing Third Grade’s Mastery of Simple Present Tense Using Flashcards - Maya Sartika (JET (Journal of English Teaching), 2020)
Mastering the simple present tense can be very difficult for EFL young learners because tenses contain abstract concepts that do not exist in the first language of EFL learners. The third graders at Permai Elementary School, North Jakarta, also encountered problems in mastering the tense when they are taught using the lecture method. To solve the problem, action research was conducted by using flashcards. The action research was carried out in two cycles in August to October 2019. Involving 30 third graders, quantitative and qualitative data were collected employing tests, observation, and questionnaires. The findings revealed that flashcards use managed to increase the students’ achievement in learning the simple present tense. The mean scores of the three tests administered during the action research increased from 36.69 to 65.73 and to 75.00. The use of flashcards also changed the students’ attitude from mainly negative to mainly positive. The mean of the positive responses increased from 20.4% in the pre-action survey to 83.89% in the post-action survey.